Genetic diversity analysis in Brassica varieties through RAPD markers (Bangladesh Journal of Agricultural Research, 2009)
This investigation was aimed at exploring the genetic diversity and relationship among nine Brassica varieties, namely BARI Sharisha-12, Agrani, Sampad, BINA Sharisha-4, BINA Sharisha-5, BARI Sharisha-13, Daulot, Rai-5, Alboglabra using Random Amplified Polymorphic DNA (RAPD) markers. In total, 59 reproducible DNA bands were generated by four arbitrary selected primers of which 58 (98.03%) bands were proved to be polymorphic. These bands ranged from 212 to 30686 bp in size. The highest proportion of polymorphic loci and gene diversity values were 37.29% and 0.1373, respectively, for BARI Sharisha-12 and the lowest proportion of polymorphic loci and gene diversity values were 8.47% and 0.0318, 8.47% and 0.0382 for BINA Sharisha-4 and Rai-5, respectively. A dendrogram was constructed using unweighted pair group method of arithmetic mean (UPGMA). The result of cluster analysis indicated that the 9 accessions were capable of being classified into 2 major groups. One group consists of BARI Sharisha-12, Agrani, Sampad, Daulot, Rai-5, Alboglabra. where Daulot and Rai-5 showed the lowest genetic distance of 0.049. And another group contains BINA Sharisha-4, BINA Sharisha-5, and BARI Sharisha-1 3, where BINA Sharisha-5 and BARI sharisha-13 showed genetic distance of 0.071. Key Words: RAPD, Brassica, genetic distance, polymorphic band. DOI: 10.3329/bjar.v34i3.3976 Bangladesh J. Agril. Res. 34(3) : 493-5032, September 2009